Monocytes, Macrophages, and Interleukin 27: Double-edged Swords in the Control and Immunopathogenesis of Chikungunya virus infection (2024)
ABSTRACT: Global warming together with an uncontrolled increase in the deforestation and growth of human populations in both urban and rural areas has converted various zoonotic and vector-borne agents into the most important causes of emerging infectious diseases worldwide. An example of this is the recent outbreaks of Chikungunya virus (CHIKV), a re-emerging arbovirus member of Togaviridae family, Alphavirus genus, which is transmitted to humans by the bites of female mosquitoes of Aedes genus. CHIKV is the etiological agent of chikungunya fever (CHIKF), a self-limiting disease that occurs in approximately 95% of individuals infected with the virus. The acute phase of CHIKF is characterized by fever and severe acute polyarthralgia and myalgia, which usually disappear 2-3 weeks after CHIKV infection. However, about 55% of the affected individuals develop a subacute or chronic state of the disease in which some arthrogenic symptoms such as joint swelling, joint stiffness, arthralgia, arthritis, and tendonitis can last for months to years. Although many aspects of CHIKV pathogenesis in humans are unknown, different reports suggest that CHIKF is associated with the development of immunopathology linked to high levels of pro-inflammatory factors. To date, the chronicity of CHIKV-dependent arthritis has been related to a strong and persistent inflammatory response. Moreover, in CHIKV-infected patients and mice, the musculoskeletal and joint tissues exhibit significant infiltration by monocytes and macrophages. These myeloid phagocytic cells, integral components of the innate immune response, play a crucial role in recognizing viral infections and inducting innate antiviral response to control viral replication into the cells and spread into the tissues. However, the role of monocytes and macrophages in the control and/or immunopathogenesis of CHIKV infection in humans is poorly understood. Therefore, the research presented in this thesis focuses on the question: What is the role of human monocytes and macrophages in the induction of innate immune pro-inflammatory and antiviral responses to CHIKV infection, and their role in the control and/or immunopathogenesis of acute and chronic CHIKF? In Chapter 1, I performed a state-of-the-art update about CHIKV biology, CHIKF pathogenesis, and the innate immune antiviral mechanisms involved in the recognition and control of CHIKV infection. Then, In Chapter 2, I describe the kinetics of CHIKV replication, cytokines production, and mRNA expression of Toll-like receptors (TLRs), Interferons (IFNs), and Interferon-stimulated genes (ISGs) in primary human monocytes and monocyte-derived macrophages (MDMs) infected with CHIKV. I found that both monocytes and MDMs are susceptible and permissive cells to CHIKV infection in vitro. Additionally, monocytes and MDMs induce differential pro-inflammatory and antiviral responses against CHIKV infection, a process dependent on the production of pro-inflammatory cytokines and the induction of ISGs-dependent antiviral response involved in the control of viral replication. However, CHIKV-infected MDMs induce antiviral response independent of IFN-I expression. Then, in Chapter 3, I described that CHIKV infection inhibits the expression of all types of IFN in human MDMs, and identified the Interleukin 27 (IL27) as a new inductor of antiviral state and control of CHIKV replication through the activation of JAK-STAT signaling pathway and the induction of ISGs. Next, in Chapter 4, I describe the molecular mechanism involved in transcriptional regulation of IL27 in CHIKV-infected MDMs. I found that IL27p28 and EBI3 genes have a differential transcriptional regulation dependent on activation of the TLR1/2-MyD88-NF-kB pathway in the case of EBI3, and TLR3-TRIF-IRF1 pathway in the case of IL27p28. Moreover, using previously published transcriptomic data of murine BMDM, and an in vitro model of human MDMs stimulated with TLR agonists, I describe a synergistic effect of MyD88- and TRIF-dependent TLRs in the induction of IL27 and the establishment of antiviral response in macrophages. Moreover, I found that TLR4, the only TLR that signals through both MyD88 and TRIF in macrophages, induces a robust antiviral response dependent on IL27 production. Considering the interferon-like antiviral properties of IL27 described in previous chapters, in Chapter 5, I performed a comparative analysis of transcriptional profile of human MDMs stimulated with the different types of IFN or IL27. I found that all types of IFN and IL27 induce activation of JAK-STAT signaling pathway promoting a common pro-inflammatory and antiviral response dependent on ISG expression, that interfered with CHIKV and DENV-2 replication in human MDMs. Therefore, in this chapter, I postulate that IL27 could be a new type of interferon, the type V IFN (IFNπ). Lastly, in Chapter 6, I have summarized and discussed the key results of this thesis. Together, the data presented in this thesis showed that human monocytes, macrophages, and IL27 play a key role in both the control and immunopathogenesis of CHIKV infection in humans and mice, by promoting innate immune pro-inflammatory and antiviral responses that implement the antiviral state in cells to control viral replication. Also, promoting robust STAT1-dependent pro-inflammatory responses which in context of chronic CHIKV infection, promotes an uncontrolled and persistent inflammatory state that contributes to the development of chronic arthrogenic signs in CHIKF patients. This suggests that regulation of monocyte/macrophage activation and/or IL27-dependent JAK-STAT signaling pathway activation are promising therapeutic targets to control the development of chronic arthralgia in CHIKF patients.